Open apex and crown fracture management - Rhona M. Untari; Kurnia Fitriningtyas; Margareta Rinastiti (Journal of Dentomaxillofacial Science, 2021)
Objective : To describe the management of a coronal complicated fracture of an upper left central incisor with pulp necrosis and open apex using MTA and restored with PFM crown with customized glass fiber post. In this case, after the apexification procedure, the root canal was not filled with gutta-percha but directly filled with customized glass fiber post. Case Report : A 14-year-old female patient came to the RSGM UGM Prof. Soedomo with chief complaints of crown fracture in the upper left central incisor and wanted to be treated. The first step of the endodontic treatment was the apexification of tooth 21 using MTA and the restoration after apexification was PFM crown with customized glass fiber post which was expected to aesthetically recover its original form and function. Result : After a year recall, the clinical appearance of the teeth 21, showed no sign of marginal inflamation or alterations of the proximal. The patient felt comfortable with his appearance and did not have tooth pain. Conclusion: Endorestoration treatment on anterior teeth with complicated crown fractures and open apex can restore the normal form, function and dental aesthetic according to a stomatognathic system and restore self-confidence.